Adequate antenatal care service utilizations after the onset of COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis - Wondmeneh, Temesgen Gebeyehu; Solomon Tadesse, Zelalem (Frontiers in Public Health, 2024)
Background The world faces great difficulty in continuing to provide essential maternity health care after the onset of COVID-19 pandemic Many women have trouble accessing maternity healthcare due to fear of infection. A decline in the utilization of maternity health services is suggested to worsen adequate antenatal care service utilization. Thus, this study aimed to determine the pooled estimate of adequate antenatal care service utilization after the onset of COVID-19 in Ethiopia. Methods The searching of articles was carried out on Web of Science, Scopus, PubMed, CINHAL, Google Scholar, African journals online, and the institutional repository of Ethiopian universities. Using a Microsoft Excel standardized spreadsheet, the data were extracted. A random effect model was used to determine a pooled estimate of adequate antenatal care utilization. I2 statistics were used to quantify the amount of heterogeneity. The evidence of publication bias was examined using Egger's regression test and a visual inspection of the funnel plot. Subgroup and sensitivity analyses were also carried out. Results Finally, this systematic review and meta-analysis included 11 eligible articles. The overall pooled estimate of adequate antenatal care service utilization after the onset of COVID-19 pandemic in Ethiopia was 46.28% (95% CI: 35.32%−57.26%). There is a substantial amount of heterogeneity between studies (I2 = 99.07%, p < 0.001). Pregnant women who visited antenatal care early were 10.9 times more likely to have adequate antenatal care utilization than those without early visits (AOR = 10.93, 95% CI: 7.2–14.66). Conclusion In this review, the percentage of women who utilized adequate antenatal care after the onset of COVID-19 pandemic in Ethiopia was less than half. Early antenatal care visit is an important factor to achieve adequate antenatal care service utilizations. Systematic review registration : CRD42023495279.